ORGANIZATIONAL AND TECHNOLOGICAL PRINCIPLES OF BUILDING A SMART PLATFORM FOR DIGITAL EDUCATIONAL ENVIRONMENT OF A MODERN UNIVERSITY - Maslova, Irina; Frolov, Aleksei; Uzharinskyi, Anron (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article presents conceptual architectural and technological solutions. In the article is justified application of technology and integration of SMART subsystems platform based on a single integrating data schema. The structure of the integrated information and computing environment, based on the classical architecture of SOA and differing by the presence of a repository of services which stores information about all available web services and the ability to remotely call the methods of services by clients.